2007
DOI: 10.1681/asn.2006121397
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Metabolism and Vascular Damage in Children on Dialysis

Abstract: Cardiovascular disease is increasingly recognized as a life-limiting problem in young patients with chronic kidney disease, but there are few studies in children that describe its determinants. We studied the association of intact parathyroid hormone (iPTH) levels and their management on vascular structure and function in 85 children, ages 5-18 years, who had received dialysis for Ն6 months. Compared to controls, dialysis patients had increased carotid intima-media thickness and pulse-wave velocity. All vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
151
7
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 198 publications
(167 citation statements)
references
References 39 publications
7
151
7
1
Order By: Relevance
“…In addition, as a consequence of residual renal function, some exist closer to their dry weight and are thus very sensitive to fluid shifts during dialysis. Combined with a poorly compliant left ventricle (29) and peripheral conduit vessels (15), UF mediates a reduction in cardiac output and BP. In the face of an attenuated coronary reserve, ischemia prevails when the hemodynamic demand of HD is not met by an adequate increase in myocardial blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as a consequence of residual renal function, some exist closer to their dry weight and are thus very sensitive to fluid shifts during dialysis. Combined with a poorly compliant left ventricle (29) and peripheral conduit vessels (15), UF mediates a reduction in cardiac output and BP. In the face of an attenuated coronary reserve, ischemia prevails when the hemodynamic demand of HD is not met by an adequate increase in myocardial blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Children and young adults with uremia have a similar constellation of ischemia-predisposing factors to adults, including increased intima media thickness and pulse wave velocity, vascular calcification, early atherosclerosis, and endothelial dysfunction (14,15), but without significant atheromatous CAD. In our experience, the incidence of HD-induced hemodynamic disturbance is comparable to adults, with a 20 to 30% incidence of intradialytic hypotension associated with a relative blood volume reduction of 20 to 25% (16).…”
mentioning
confidence: 99%
“…PWV has recently become a focus of interest in a number of clinical conditions where functional and morphological alterations of the arterial tree are of prognostic relevance. Consistent changes in PWV have been observed in children and adults with end-stage renal disease [3][4][5][6][7], diabetes mellitus [8,9], and vasculitis [10][11][12]. Arterial stiffness has been attributed independent prognostic significance.…”
Section: Clinical Relevance Of Pwvmentioning
confidence: 74%
“…Therefore, the continuous elevation of PWV appeared to be predictive of the renal outcome, whereas laboratory markers such as hypocomplementemia and antistreptolysin titers were not. PWV has been shown to be increased in chronic kidney disease [3][4][5][6][7], and the observation of Yu et al might simply reflect chronic kidney disease without any specificity for the underlying disorder. In addition, persistently elevated blood pressure might have confounded the association.…”
Section: Prognostic Relevance Of Pwvmentioning
confidence: 99%
“…Amongst children with CKD, both cardiac [5] and vascular damage and calcification [6] are present from the pre-dialysis CKD stages, and these increase in prevalence and severity on dialysis [6]. Importantly, all paediatric and adult studies conducted to date have shown that CVD progression with deteriorating cardiac function and progressive vascular calcification is associated with a long dialysis vintage [1,3,[6][7][8][9][10][11] on both haemodialysis (HD) and peritoneal dialysis (PD).…”
Section: Introductionmentioning
confidence: 99%